Acetylation phenotype variation in pediatric patients with atopic dermatitis - Rafi A Majeed Al-Razzuqi; Ali A Al-Jeboori; Makram M Al-Waiz (Indian Journal of Dermatology, 2011)
Background: Few studies have been done on the relation between acetylator status and allergic diseases. Aim: To determine any possible association between acetylating phenotype in pediatric patients with atopic dermatitis (AD) and the disease prognosis. Patients and Methods: Thirty-six pediatric patients and forty two healthy children as a control group were participated in the study. All participants received a single oral dose of dapsone of 1.54 mg/kg body weight, after an overnight fast. Using high performance liquid chromatography (HPLC), plasma concentrations of dapsone and its metabolite (monoacetyldapsone) were estimated to phenotype the participants as slow and rapid acetylators according to their acetylation ratio (ratio of monoacetyldapsone to dapsone). Results: 72.2% of pediatric patients with AD showed slow acetylating status as compared to 69.4% of control individuals. Also, 73% of AD patients with slow acetylating phenotype had familial history of allergy. The severity of AD occurred only in slow acetylator patients. The eczematous lesions in slow acetylators presented mainly in the limbs, while in rapid acetylators, they were found mostly in face and neck. Conclusion: This study shows an association between the N-acetylation phenotype variation and clinical aspects of AD.